Innovative approach to measuring meaningful learning in digital TVET - Tahir, Raihan (Journal of Islamic, Social, Economics and Development, 2025)
Digitalization and Industry 4.0 require a shift from traditional assessment methods to more authentic, competency-based evaluations that are aligned with real-world applications. As industry processes evolve through advanced technologies, the need for a new assessment approach in TVET becomes increasingly evident. Traditional assessments, often summative and content-focused, are inadequate in capturing the skills and competencies necessary for students to thrive in modern industries. Authentic assessments, which integrate realistic work tasks, collaborative problem-solving, and cognitive complexity, offer a more relevant means of assessing student learning. These assessments enable students to demonstrate their technical skills in contexts that mirror workplace challenges, while also showcasing competencies that reflect their learning journey. This approach not only aligns with industry standards but also fosters critical thinking, innovation, and engagement. Supported by evidence-based expert recommendations, this study explores innovative approaches to enhance TVET quality, ensuring the development of Industry 4.0-ready talents. The study gathered insights from nine experts for the Nominal Group Technique (NGT) and Interpretive Structural Modelling (ISM), and each expert with over ten years of experience in mechanical and manufacturing-related diploma programmes from both public and private TVET institutes in Malaysia. These experts bring a wealth of diverse perspectives from portfolios that include curriculum development, assessment, media, industry advisory, teacher training, and management. The findings revealed three prioritized strategies to be adopted: 1) Authentic and Task-Specific Assessments, 2) Process and Procedural Evaluation, and 3) Criterion-Referenced and Rubrics-Based Assessments. By adopting these strategies, TVET institutions can more effectively evaluate students' competencies in ways that mirror the dynamic and evolving demands of the world of work. This article provides actionable strategies and insights for educational leaders and instructors, offering an innovative approach to align assessment practices with the evolving needs of technology-driven industries.